Experimental Determination of Heat Transfer Coefficient in Stirred Vessel for Coal-Water Slurry Based on the Taguchi Method. (23rd June 2013) - Raguraman, C. M.; Ragupathy, A.; Sivakumar, L.
Abstract : Heat transfer in stirred vessels is important because process fluid temperature in the vessel is one of the most significant factors for controlling the outcome of process. In this study, the effects of some important design parameters for coal-water slurry in agitated vessel used in coal gasification such as stirrer speed, location of stirrer, D/d ratio, and coal-water ratio were investigated and optimized using the Taguchi method. The experiments were planned based on Taguchi's L 9 orthogonal array with each trial performed under different levels of design parameter. Signal-to-noise (S/N) analysis and analysis of variance (ANOVA) were carried out in order to determine the effects of process parameter and optimal factor's level settings. Finally, confirmation tests verified that the Taguchi method achieved optimization of heat transfer coefficient in agitated vessel.